MAKE APPLICATION ON STUDENT TEST PERFORMANCE ELEMENTARY ARITHMETIC USING MICROSOFT VISUAL BASIC 6.0 - Fahrul Rozi; Eko Hadiyanto, SSi, MMSi Eko Hadiyanto, SSi, MMSi (Jurnal Sistem Informasi, 2004)
The growing use of computer media today are not only used for typing activities, but can also be used to support teaching and learning process. In scientific writing, the writer makes a simple application that is used to test the ability of a person in Arithmetic operations. This application will tell us how fast a person can perform the arithmetic operations.